Smartphone Blast Ocular Injury During Long Term Gaming Addiction in Children after the COVID era - Santosh Singh Patel; Sushil Sachdeo; Reshu Malhotra; Vaibhav Vishal (Delhi Journal of Ophthalmology)
In its aftermath, the COVID era has left society addicted to smartphones and made us susceptible to injury caused by exploding batteries. These phones use high-density batteries with a long life cycle and are relatively safe despite the potential risk of explosion. Ignition in a lithium-ion battery can occur due to various causes. The failure rate of lithium batteries is extremely low at 1 in 10 million, but in a society with the ever-increasing use of smart devices, this low potential is very real and debilitating. We are presenting a case of a smartphone battery explosion injury in a young 11-year-old child caused by overuse in the charging position, which resulted in a corneal and lid tear of the left eye and loss of digits in the right hand and lacerated wound in the index finger of his left hand. There is an urgent need for creating awareness against such incidences for prevention and prompt management of debilitating injuries that may follow. There is also a need to create awareness about proper usage and battery optimization for the safety of the user.